Hydrogen induced cold cracking of creep resistant ferritic P91 steel for different diffusible hydrogen levels in deposited metal. (19th October 2016) - Pandey, Chandan; Saini, Nitin; Mahapatra, M.M.; Kumar, Pradeep
Abstract: Hydrogen-assisted cracking (HAC) is a serious issue in P91 steel welds because of unwanted martensitic metallurgical-transformation in the heat affected zone (HAZ). In the present research, different electrode conditions have been employed during welding of P91 steel to study their effects on HAC. The HAC susceptibility of cast and forged (C&F) P91 steel welds produced by shielded metal arc welding (SMAW) process has been evaluated through implant test with respect to the different level of diffusible hydrogen content in the deposited metal. The weld implant test results such as applied stress vs time to failure, the lower critical stress (LCS), embrittlement index (EI) and normalized critical stress ratio (NCSR) were evaluated with respect to the different level of hydrogen content in the deposited metal. The microstructure of coarse grain heat affected zone (CGHAZ) and weld metal in different condition have been characterized by using scanning electron microscope (SEM). The fracture morphology of implant specimen was characterized by using the SEM. The paper also describes the effect of hydrocarbon contamination (oil or grease) in low-hydrogen basic SMAW electrode for P91 steel. It can be concluded that P91 steel welded by the electrode having higher contamination (high hydrogen level) is more susceptible to HAC. The LCS value was observed to be decreasing with the increase in the diffusible hydrogen content in deposited metal and minimum value was measured to be 180 MPa for 12.54 ml of diffusible hydrogen per 100 g of deposited metal. Graphical abstract: Highlights: Diffusible hydrogen measurement of SMAW P91 deposits for varying electrode conditions. Measurement of lower critical stress (LCS). Effect of diffusible hydrogen on LCS, embrittlement index (EI) and critical stress ratio. Effect of diffusible hydrogen on microstructure of weld fusion and heat affected zone. Fracture morphology of implant specimen for different diffusible hydrogen content.